2018
DOI: 10.1101/378745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stabilizing Obligatory Non-native Intermediates Along Co-transcriptional Folding Trajectories of SRP RNA Affects Cell Viability

Abstract: SummarySignal recognition particle (SRP) in Escherichia coli comprises protein Ffh and SRP RNA. Its essential functionality-co-translational protein-targeting/delivery to cellular membraneshinges on the RNA attaining a native long-hairpin fold that facilitates protein conformational rearrangements within the SRP complex. Since RNA folds co-transcriptionally on RNA polymerase, we use high-resolution optical tweezers to first characterize the mechanical unfolding/refolding of incrementally lengthened RNAs from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…This hairpin rearranges into the long helical structure, which DUETT identifies as downswing events between lengths 116 and 127 nt in bases 11, 14-15, and 17-19. These identifications are consistent with recent computational modeling (Yu et al, 2018) and single molecule optical tweezer experiments (Fukuda et al, 2018) that propose the rearrangement of H1 to occur in the window that DUETT detects.…”
Section: Duett Identifies Expected H1 Formation and Rearrangementsupporting
confidence: 89%
See 3 more Smart Citations
“…This hairpin rearranges into the long helical structure, which DUETT identifies as downswing events between lengths 116 and 127 nt in bases 11, 14-15, and 17-19. These identifications are consistent with recent computational modeling (Yu et al, 2018) and single molecule optical tweezer experiments (Fukuda et al, 2018) that propose the rearrangement of H1 to occur in the window that DUETT detects.…”
Section: Duett Identifies Expected H1 Formation and Rearrangementsupporting
confidence: 89%
“…Previous studies have shown that during transcription, the E.coli SRP RNA forms a transient 5' hairpin (H1) that rearranges into a long helical structure with a hairpin loop and multiple inner loops (Batey et al, 2000;Wong et al, 2007;Watters, Strobel, et al, 2016), which we label H2-H5 ( Figure 2). Several of these transitions have been validated by prior bulk studies (Wong et al, 2007;Watters, Strobel, et al, 2016), and by single molecule optical trapping experiments (Fukuda et al, 2018). A previous Here DUETT is applied to a mock dataset to identify an increase in reactivities in several consecutive nucleotides which is consistent with the typical 'low-high-low' pattern observed for RNA hairpin structures.…”
Section: Validation On E Coli Srp Rna Cotranscriptional Shape-seq Damentioning
confidence: 81%
See 2 more Smart Citations
“…However, local off-pathway folds are unexpected for riboswitch folding pathways since function requires successful aptamer folding and therefore mandates that non-native intermediates be resolved efficiently. Despite this, we observed that pfl riboswitch folding involves formation of the temporary helix IH1, which precedes P1 folding, making this one of the few examples of non-native intermediate folds have been experimentally observed (Fukuda et al, 2018;Incarnato et al, 2017;Wong et al, 2007;Yu et al, 2018) (Figure 2). Interestingly, the IH1 structure is not explicitly encoded in the pfl aptamer consensus sequence.…”
Section: Discussionmentioning
confidence: 65%